Nurses' demands and resources at work: workload, workplace friendship, positive affect, work engagement on performance - Andika, Wahyu; Daud, Ilzar; Azazi, Anwar; Setiawan, Harry; Fitriana, Ana (Enrichment : Journal of Management, 2023)
This study delves into how nurses perceive the demands and resources of their jobs, aiming to uncover their impact on job performance and engagement. The focus is on how nurses deal with workload, workplace friendships, and positive affect influencing their engagement and performance. These relationships were tested using Structural Equation Modeling assisted by the AMOS 24 statistical tool. The sample was drawn with purposive sampling from nurses recruited by health centers in West Kalimantan, Indonesia (n=213). The study found that workload was perceived as having a negative impact on performance, while workplace friendship, positive affect, and work engagement had a positive impact. Furthermore, the workload had a negative impact on work engagement, while workplace friendship and positive affect had a positive effect. In addition, work engagement partially mediates the relationship to performance; workload continues to have a negative effect, while workplace friendship and positive affect continue to have a positive effect. The negative relationship of workload to performance and engagement means nurses at health centers in West Kalimantan perceive workload as a job demand that particularly hinders them, while positive relationship of workplace friendship and positive affect act as resources that motivate their work.